Nurse Practitioners' Self-Efficacy and Behavior in Supporting Self-Management of Patients With a Progressive, Life-Threatening Illness and Their Relatives: A Nationwide, Cross-Sectional Online Survey. Issue 4 (5th August 2022) - Arslan, Muzeyyen; van Dongen, Sophie I.; Witkamp, Erica; van Hooft, Susanne M.; Billekens, Pascalle; Kranenburg, Leonieke W.; Stoevelaar, Rik; van der Rijt, Carin C.D.; van Dijk, Monique; van der Heide, Agnes; Rietjens, Judith A.C.
Abstract : This study aimed at investigating nurse practitioners' self-efficacy and behavior in supporting self-management of patients with a progressive, life-threatening illness and their relatives. We adapted an existing validated instrument for this purpose, amongst other things by adding a seventh subscale "attention for relatives, " and administered it in a nationwide, cross-sectional online survey among Dutch nurse practitioners. We analyzed associations between self-reported self-efficacy and behavior using Pearson correlations and paired sample t tests. Associations between self-efficacy and behavior with nurse practitioners' characteristics were examined using linear regression models. Most nurse practitioners (n = 327; 26% complete responses) were women (93%). Subscale and total scores for nurse practitioners' self-efficacy were moderately positively correlated with those for their behavior in self-management support. Subscale and total scores were statistically significantly higher for their self-efficacy than for their behavior. Increased work experience with patients with a progressive, life-threatening illness was associated with higher scores on self-efficacy and behavior in self-management support. We conclude that nurse practitioners are confident in their ability to support self-management; yet, they do not always use these competencies in practice.